Making democracy work in a refugee camp: social capital and the emergence of empowerment. Issue 3 (3rd April 2023) - Feinstein, Scott; Poleacovschi, Cristina
ABSTRACT: Since 2015, over one million refugees sought refuge in Europe and around 70, 000 refugees have been hosted in refugee camps in Greece. Refugees' empowerment is threatened in these camps as they have restricted access to resources and decision making. This research argues that social capital plays an important role in refugees' sense of empowerment. The research uses a mixed-methods case study of a refugee camp in Greece, including 20 interviews and 38 surveys to assess refugees' sense of empowerment and social capital. The results showed that bridging and linking social capital enhances a sense of empowerment while bonding does not.